MERUMUSKAN KONSEP ISLAM BERKEMAJUAN SEBAGAI PARADIGMA PEMBARUAN PEMIKIRAN ISLAM KONTEMPORER DI INDONESIA - Nur Aliah; St Nurhayati; Sudirmanto Sudirmanto (Jurnal Manajemen Pendidikan, 2026)
Objective:  This study aims to formulate the concept of Progressive Islam as a paradigm for the renewal of contemporary Islamic thought in Indonesia. The concept developed by Muhammadiyah is understood as a response to the challenges of modernity, globalization, and increasingly complex socio-religious dynamics. This research employs a qualitative approach using library research methods. Data were collected through literature studies from books, scientific journals, and relevant official documents, then analyzed using content analysis techniques to identify the concepts, characteristics, and relevance of Progressive Islam in the contemporary context. The findings indicate that Progressive Islam is a paradigm emphasizing the integration of tawhid values, rationality, openness to scientific advancement, religious moderation, and orientation toward social justice and public welfare. This paradigm also highlights the importance of contextual ijtihad in responding to contemporary issues such as pluralism, democracy, intolerance, and technological development. The novelty of this study lies in formulating Progressive Islam as an epistemological paradigm that is not only normative-theological but also transformative, inclusive, and applicable in Indonesian social life.